Repopulation of the gut microbiota after a screening colonoscopy - Yezaz A. Ghouri; Aaron C. Ericsson; Jennifer M. Anderson; Jessica G. George; Elizabeth J. Parks; Katherene O. B. Anguah (PLoS ONE, 2025)
Objective Role of microbiome has been highly studied for its association with various medical conditions. After a colonoscopy, repopulation of colonic microbial load is known to occur, however the quality and timing of natural repopulation has not been investigated after a bowel preparation. Further, no study has documented detailed free-living dietary intakes concurrently with gut microbiome repopulation post-colonoscopy. Here we sought to determine the early pattern of repopulation relative to dietary intake. Methods Healthy adults (n = 15 [4 female/11 male], BMI = 27.2 ± 3.9 kg/m2, age 51.4 ± 7.2 y) who were scheduled to undergo a screening colonoscopy were recruited from the Gastroenterology Clinic at the University of Missouri. Within two weeks before the colonoscopy (baseline), subjects completed detailed food records for 3 days. Post-colonoscopy, subjects ate their free-living diets and detailed food records were collected on Days 0, 1, 2, 4, 7, 10, and 13. Fecal samples were obtained pre-colonoscopy and on post-colonoscopy Days 3, 5, 8, 11, and 14. Gut microbiome composition was assessed by 16S rRNA amplicon sequencing. Results Within 5 days after the procedure, subjects reported consuming more total daily energy relative to baseline, presumably to make up for the low energy intake that occurred during the bowel-prep. At baseline, fiber intake (21.0 ± 9.1 g/d) was higher than on the day of the colonoscopy, Day 0 (16.1 ± 11.2, P = 0.0159). Thereafter, daily fiber intake was the same as baseline. Marked intersubject microbiome beta diversity was observed by principal coordinate analysis using weighted and unweighted dissimilarities (P = 0.0001, F = 15.23, one-way PERMANOVA). Select taxa were depleted acutely post-colonoscopy (e.g., within the phylum Bacillota). Specifically, significant effects of time were observed between baseline and Day 3 fecal samples (pairwise P = 0.0013, F = 2.9). These changes tended to return to baseline by Day 5 and with subsequent samples, taxa remained similar to baseline when tested using a weighted dissimilarity analysis (Bray-Curtis). Conclusions These results quantitatively demonstrate the magnitude of the significant changes in microbial relative abundance and diversity immediately post-colonoscopy. The timing of repopulation aligned with changes in fiber intake after the procedure. These data highlight the importance of nutrition after a screening colonoscopy in reestablishing a healthy microbiome.